The total occlusal convergence of the abutment of a partial fixed dental prosthesis: A definition and a clinical technique for its assessment - Mamoun, John S. (European Journal of Dentistry, 2013)
The abutment(s) of a partial fixed dental prosthesis (PFDP) should have a minimal total occlusal convergence (TOC), also called a taper, in order to ensure adequate retention of a PFDP that will be made for the abutment(s), given the height of the abutment(s). This article reviews the concept of PFDP abutment TOC and presents an alternative definition of what TOC is, defining it as the extent to which the shape of an abutment differs from an ideal cylinder shape of an abutment. This article also reviews experimental results concerning what is the ideal TOC in degrees and explores clinical techniques of estimating the TOC of a crown abutment. The author suggests that Dentists use high magnification loupes (×6-8 magnification or greater) or a surgical operating microscope when preparing crown abutments, to facilitate creating a minimum abutment TOC.
Keywords: Convergence; dentistry; microscopes; occlusal; taper; total